Census Anesthesiology - 2014 | Final Report - Lemos, Paulo; Lima, Joaquim Figueiredo; Viana, Joaquim; Assunção, José Pedro; Veiga, José; Chedas, Manuel; Sousa, Manuel Costa; Branca, Pedro; Abrunhosa, Rosário; Almeida, Valentina (Journal of the Portuguese Society of Anesthesiology, 2015)
The current perception that there is an important shortage of anesthesiologists in Portugal, led the Board of the Portuguese College of Anesthesiology to carry out a national survey on May 2014. All Head of Anesthetic Departments of the Public Hospitals included in the Portuguese National Health Service (NHS), whatever the type of management used were contacted. Fifty two Portuguese Public Hospitals were included (from inland including the three oncologic hospitals and the two military hospitals in Lisbon and Porto, to the Islands of Azores and Madeira with four publics hospitals). Data related to organizational, human resources and logistic were asked to report to the week between 12 and 18 May 2014, and the annual numbers related to operational results coming from 2013. A simplified version of the national survey was sent to the Clinical Director of the Portuguese Private Hospitals, with the aim to identify all anesthesiologists working in an exclusive basis in the private system. Hospitals analyzed which of them 82.8% on a non-emergent basis, and from these 43.5% in a day surgery basis. Moreover, authors realize that 110,668 procedures were performed outside the operating rooms, 279,205 were anesthetic clinics and 99,153 were chronic pain evaluations. In addition, 44,956 analgesia for delivery were performed, which might correspond to about 65% of all deliveries occurred in the Obstetric Department of Portuguese Hospitals, Public and Private in 2013. One thousand, one hundred and twenty one anesthesiologists working at the Anesthetic Departmentof the Portuguese Public Hospitals analyzed were identified. In addition, authors registered 71 anesthesiologists working in those hospitals but outside the Anesthetic Department (mainly in intensive care units or chronic pain units), and 62 new specialists in Anesthesiology were waiting to celebrate a contract with one of the Hospitals, making a total figure of 1,254 Anesthesiologists working in the Public Portuguese NHS, which correspond to a 12.0 per 100,000 inhabitants ratio. If we consider that 200 anesthesiologists are working in May 2014 in the private system, this means that the current ratio is 13.9 per 100,000 inhabitants. The Head of Anesthetic Department of the Public Hospitals included in the Portuguese NHS altogether appointed a value of 467 anesthesiologists that are presently needed in their hospitals to face the daily needs on anesthetic services care. Authors predict that by 2020, this value will be reduced in two thirds allowing an increase capacity in human resources in Anesthesiology and an important working force to face the future with some optimism.